Mapping Strategic and Sustainable Relevant Actors of Poultry Production and Business Using Stakeholder Network Analysis - Desni Triana Ruly Saragih; Meky Sagrim; Hendrik Fatem; Stepanus Pakage; Yosina Waromi; Daniel Seseray; Aisyah Bauw; Hendrik Arwam; Miksen Sangkek; Deny Iyai (Jurnal Agripet, 2020)
ABSTRACT. Stakeholders and their network place top rank of value chain business and ruled prominent roles in the livestock development sector particularly poultry commodity. The involvement of many stakeholders and other parties is questionable because they perform and shape the market and business chain. The study was done in Manokwari using focus group discussion towards twenty-four various represented individuals, groups and mass organizations. The key queries discussed concerning the introduced background of the organization, shared resources, inter-connectivity amongst actors, intervention and innovation preferences and shared by actors. Stakeholder Network Analysis was employed to run the network and relationship between actors using the Pearson Correlation Coefficient and Hierarchical Clustering Analysis. The finding is that the stakeholders in the poultry farming systems are dominated by private group actors who are working in groups to manage the farms and its value chain process and officially have been under laws. These actors commonly act like positive important stakeholders, who ruled the farms. The threats are real and exist and should be lowering as much as possible to mitigate the turn-back effect. The top five shared resources are access, spaces, time, policy, knowledge and skills. Those resources will stay longer to sustain the strong needs of poultry farms. The relationship of actors is dominated by the ranges of correlation are varying in between negative, neutral to positive. Actors are not delivering the intervention and innovation yet. Actors with low interest and low power should then be promoted to high interest and high power by using aids, guidance, and services from each actor from its value chain and cooperation and farming business. (Pemetaan Pemangku Produksi dan Bisnis Unggas Strategis dan Berkelanjutan Dengan Aplikasi Analisis Jaringan Stakeholder) ABSTRAK. Pemangku kepentingan dan jaringannya menempati peringkat teratas dalam bisnis rantai nilai dan memegang peran penting dalam sektor pengembangan peternakan khususnya komoditas unggas. Keterlibatan banyak pemangku kepentingan dan pihak lain patut dipertanyakan. Penelitian dilakukan di Manokwari dengan menggunakan FGD terhadap dua puluh empat perwakilan individu, kelompok dan ormas. Pertanyaan utama membahas tentang latar belakang organisasi yang diperkenalkan, sumber daya bersama, interkoneksi antar aktor, preferensi intervensi dan inovasi dan dibagikan oleh aktor. Analisis Jaringan Pemangku Kepentingan digunakan untuk menjalankan jaringan dan hubungan dengan menggunakan Koefisien Korelasi Pearson dan Analisis Pengelompokan Hirarkis. Temuannya adalah bahwa para pemangku kepentingan dalam sistem peternakan unggas didominasi oleh pelaku kelompok swasta yang bekerja dalam kelompok untuk mengelola peternakan dan proses rantai nilainya dan secara resmi berada di bawah undang-undang. Aktor ini biasanya bertindak seperti pemangku kepentingan penting yang positif, yang mengatur pertanian. Ancaman itu nyata dan ada dan harus diturunkan sebanyak mungkin untuk mengurangi efek balik. Lima sumber daya bersama teratas adalah akses, ruang, waktu, kebijakan, pengetahuan, dan keterampilan. Sumber daya tersebut akan bertahan lebih lama untuk menopang kebutuhan kuat peternakan unggas. Hubungan antar aktor didominasi oleh rentang korelasi yang bervariasi antara negatif, netral hingga positif. Para pelaku belum melakukan intervensi dan inovasi. Pelaku dengan kepentingan rendah dan kekuasaan rendah kemudian harus dipromosikan menjadi kepentingan tinggi dan kekuasaan tinggi dengan menggunakan bantuan, bimbingan, dan layanan dari masing-masing pelaku dari rantai nilai dan koperasi dan usaha tani.